Noviemeter Diagnostic Test as a Head Circumference Measurement Device for Under-Five Children - Novita Ayu Indraswati; Ma’mun Sutisna; Achmad Suardi; Hidayat Wijayanegara; Leri Septiani; Herry Garna (Universitas Islam Bandung, 2021)
The current typical practice for measuring the head circumference of under-five children is by using a measuring tape. However, it may create some difficulties as children cry and move during measurement, leading to less accurate results. Accurate head circumference measurement is essential for assessing brain development and early detection of brain development disorders. Therefore, a more accurate device to measure head circumference is needed. Noviemeter is a non-touch digitalized head circumference measuring device that enables easier measurement in under-five children. As a new tool, noviemeter’s accuracy, sensitivity, and specificity must be determined. This study aimed to analyze the difference in the head of under-five children circumference measurement results between a typical measuring tape as the gold standard and noviemeter and determine the accuracy, sensitivity, and specificity of the noviemeter. It was a cross-sectional analytical study using cluster random sampling on 72 under-five children in the work area of Guntung Payung Public Health, South Kalimantan, during August 2020. The measurement was performed twice, first using a measuring tape and, second, using a noviemeter. Data were analyzed statistically using the dependent t test and diagnostic test. No significant difference was found between the results of the two measuring devices (p=0.257). The sensitivity, specificity, and accuracy of the noviemeter were 87.0%, 88.4%, and 91.8%, respectively. Thus, noviemeter has good sensitivity, specificity, and accuracy as an easier alternative device to measure head circumference in under-five children. UJI DIAGNOSTIK NOVIEMETER SEBAGAI ALAT PENGUKUR LINGKAR KEPALA BALITAPraktik pengukuran lingkar kepala balita yang umum dilakukan saat ini adalah dengan menggunakan pita ukur. Akan tetapi, hal itu dapat menimbulkan beberapa kesulitan karena anak menangis dan bergerak selama pengukuran yang menyebabkan hasil yang kurang akurat. Pengukuran lingkar kepala yang akurat sangat penting untuk menilai perkembangan otak dan deteksi dini gangguan perkembangan otak. Oleh karena itu, diperlukan alat yang lebih akurat untuk mengukur lingkar kepala. Noviemeter merupakan alat pengukur lingkar kepala digital non-sentuh yang memungkinkan pengukuran lebih mudah pada anak balita. Sebagai alat baru, akurasi, sensitivitas, dan spesifisitas noviemeter harus ditentukan. Penelitian ini bertujuan menganalisis perbedaan hasil pengukuran lingkar kepala balita antara pita ukur tipikal sebagai baku emas dan noviemeter serta mengetahui akurasi, sensitivitas, dan spesifisitas dari noviemeter tersebut. Jenis penelitian ini adalah cross-sectional analytical dengan menggunakan cluster random sampling pada 72 balita di wilayah kerja Puskesmas Guntung Payung Kalimantan Selatan selama bulan Agustus 2020. Pengukuran dilakukan dua kali, pertama menggunakan pita pengukur dan kedua menggunakan noviemeter. Data dianalisis secara statistik menggunakan uji t dependen dan uji diagnostik. Tidak ditemukan perbedaan yang signifikan antara hasil kedua alat ukur (p=0,257). Sensitivitas, spesifisitas, dan akurasi noviemeter masing-masing adalah 87,0%; 88,4%; dan 91,8%. Dengan demikian, noviemeter memiliki sensitivitas, spesifisitas, dan akurasi yang baik sebagai alat alternatif yang lebih mudah untuk mengukur lingkar kepala pada anak balita.